2017
DOI: 10.1002/aenm.201701471
|View full text |Cite
|
Sign up to set email alerts
|

Balancing High Open Circuit Voltage over 1.0 V and High Short Circuit Current in Benzodithiophene‐Based Polymer Solar Cells with Low Energy Loss: A Synergistic Effect of Fluorination and Alkylthiolation

Abstract: from over 11% [1,2] and 12% [3] up to over 13% now [4] in either tandem or single junction solar cells from benzo [1,2-b:4,5-b′] dithiophene (BDT)-based polymers as the donor material in photovoltaic (PV) devices, their limiting open-circuit voltage (V oc , below 1.00 V) is still one of the key obstacles to achieve ideally high PV performance with minimized trade-off on another characteristic features of the OPV devices, i.e., the short-circuit current density (J sc ). For the first two single junction polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…Also in this case the fall of J sc is the ground of the poorer performances of mFIID and oFIID, due to the low hole mobility determined by the distortion from planarity between the phenyl pendant rings and the main conjugated chain induced by fluorine atom, especially in the ortho position. On contrary, the introduction of fluorine atoms on thiophene based pendant chain in 4′ position (PBQ‐4F, PM6, PBDTT‐SF‐BDD, PBDTT‐SF‐TT) or in both 4′ and 3′ positions [PBDTT( FF )‐ttTPD] seems not to show the drawbacks related to fluorination of pendant benzene rings. In DA copolymer PBQ‐4F both pendant thiophene moieties on the donor units and quinoxaline acceptor units bear fluorine substituents leading to devices (PC 71 BM as the acceptor and Ca/Al cathode) with high V oc (0.88 V), J sc (13.26 mA/cm 2 ), FF (70.10 %) and excellent PCE (8.18 %).…”
Section: Organic Fluorinated Materials For Photovoltaicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in this case the fall of J sc is the ground of the poorer performances of mFIID and oFIID, due to the low hole mobility determined by the distortion from planarity between the phenyl pendant rings and the main conjugated chain induced by fluorine atom, especially in the ortho position. On contrary, the introduction of fluorine atoms on thiophene based pendant chain in 4′ position (PBQ‐4F, PM6, PBDTT‐SF‐BDD, PBDTT‐SF‐TT) or in both 4′ and 3′ positions [PBDTT( FF )‐ttTPD] seems not to show the drawbacks related to fluorination of pendant benzene rings. In DA copolymer PBQ‐4F both pendant thiophene moieties on the donor units and quinoxaline acceptor units bear fluorine substituents leading to devices (PC 71 BM as the acceptor and Ca/Al cathode) with high V oc (0.88 V), J sc (13.26 mA/cm 2 ), FF (70.10 %) and excellent PCE (8.18 %).…”
Section: Organic Fluorinated Materials For Photovoltaicsmentioning
confidence: 99%
“…Copolymer PBDTT‐SF‐BDD reaches 9.72 % PCE in fullerene based OSCs characterized by high values of V oc (0.97 V) and J sc (14.70 mA/cm 2 ). This favorable balance between V oc and J sc may derive from a synergistic effect of the presence of fluorine atom and thioalkyl group on the pendant thiophene ring.…”
Section: Organic Fluorinated Materials For Photovoltaicsmentioning
confidence: 99%
“…The prepared PSCs show a PCE of 5.5% with a low V OC of 0.73 V, and through replacing alky‐thienyl side groups with meta‐alkoxy‐phenyl side groups on BDT units, the photovoltaic performance of PSCs based on the modified polymer PBFZ‐OP has effectively improved with a V OC of 0.91 V . Another verified way to lower the HOMO of benzodithiophene units is to fluorinate the conjugated thienyl side chain of benzodithiophene unit (BDT‐2F) . Zhang et al reported a wide bandgap polymer based on BDT‐2F and constructed a ITIC‐based non‐fullerene PSC, which showed a PCE of 10.4% and a V OC of 0.89 V .…”
Section: Introductionmentioning
confidence: 99%
“…To obtain high‐performance PSCs, it is very important to develop efficient p ‐type donor polymers because it plays a vital role in determining photovoltaic performances of the corresponding PSCs. The development of novel conjugated polymers possessed the donor–acceptor (D–A) motif is highly efficient to achieve high PCEs . Regulation of the electron‐donating strength of a D unit or/and electron‐withdrawing strength of an A unit in D–A copolymers has been demonstrated as an effective approach to obtain ideal optoelectronic properties, such as broad absorption spectra, low bandgaps, low‐lying highest occupied molecular orbital (HOMO) energy level, high carrier mobilities, and so forth, because of their strong intramolecular charge‐transfer (ICT) effect along the conjugated backbones .…”
Section: Introductionmentioning
confidence: 99%
“…Before long, Cao group reported on a series of MBG D–A copolymers ( E g opt ≈ 1.9 eV) based on BDT and naphtho[1,2‐c:5,6‐c]bis(2‐octyl‐[1,2,3]triazole) (TZNT) units with a high PCE up to 7.11% in an inverted BHJ F‐PSCs . Besides FBTA and TZNT groups, other weak A units have also been used to build MBG D–A copolymers for high‐performance F‐PSC applications, such as benzodithiophene‐4,8‐dione (BDD), dithienobenzochalcogenadiazole, and so forth. Currently, MBG D‐A copolymers are very popular in NF‐PSCs as one of donor materials.…”
Section: Introductionmentioning
confidence: 99%